2021
DOI: 10.1002/poi3.250
|View full text |Cite
|
Sign up to set email alerts
|

The regulation of internet pornography: What a survey of under‐18s tells us about the necessity for and potential efficacy of emerging legislative approaches

Abstract: In 2017, the UK Parliament passed an Act requiring legal pornographic websites to implement 'robust' age verification checks. Although the Act inspired lawmakers elsewhere to propose similar legislation, it was never enacted, in part because it did not cover social media platforms. Instead, the UK government has turned to its Online Harms White Paper-which does target social media platforms-to protect children from online pornography. There is, however, scant evidence on the media platforms and technologies ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
2
10
0
1
Order By: Relevance
“…This is important, given that emerging legislative and regulatory attempts to limit the access to legal online pornography differ in the media platforms they target. This study's findings are, in some regards, in line with similar research from the UK (Thurman & Obster, 2021). The combined findings show, firstly, that dedicated pornographic sites are the most frequent source of pornography for UK and French adolescents, and that a substantial minority have visited such sites; and, secondly, that other online platforms, in particular social media and search engines, are also sources of pornography for substantial minorities or even majorities, although not as recently.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is important, given that emerging legislative and regulatory attempts to limit the access to legal online pornography differ in the media platforms they target. This study's findings are, in some regards, in line with similar research from the UK (Thurman & Obster, 2021). The combined findings show, firstly, that dedicated pornographic sites are the most frequent source of pornography for UK and French adolescents, and that a substantial minority have visited such sites; and, secondly, that other online platforms, in particular social media and search engines, are also sources of pornography for substantial minorities or even majorities, although not as recently.…”
Section: Discussionsupporting
confidence: 91%
“…It is also plausible that, if access to dedicated pornographic websites became more difficult, then there could be displacement to other media platforms on which pornography can be found. As this and other surveys (Thurman & Obster, 2021) have shown, Western European adolescents are being exposed to pornography on other platforms such as social media, search engines, YouTube, and messaging apps, and even offline, via magazines and DVDs (albeit infrequently among a small minority).…”
Section: Discussionmentioning
confidence: 61%
“…The most common harmful activities among youth aged 10–17 included cyberbullying (32%–65%; Skierkowski-Foster, 2021; Zhu et al , 2021) and digital dating abuse (12%–83%; Rodriguez-Castro et al , 2021; Stonard, 2020), with the majority of these engagements occurring on encrypted messaging such as WhatsApp (Aizenkot, 2020; Lara, 2020). Media piracy (47%–68%) and the use of virtual private networks to access forbidden content (46%) were also highly prevalent (Thurman and Obster, 2021; Udris, 2016). While juvenile hacking showed a lower prevalence rate at just under 8%, the debut age is low, with 90% completing their first hack before age 15 (Fox and Holt, 2021), and a lifespan implication as 61% of adult hackers reported their debut hack below age 16 (National Crime Agency UK, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Age restrictions on viewing and uploading pornographic material vary globally; studies from countries with prohibitions on underage use report that viewing and uploading pornography is a common online activity for adolescents, who may use virtual private networks (VPNs) to subvert age restrictions (Chen et al , 2021; Choi et al , 2017). A UK study found that 46% of surveyed teens aged 16–17 years used VPNs to view age-restricted websites (Thurman and Obster, 2021). A survey of 3,780 families in North America, Europe and Russia with children aged 8–16 years found that 20% of 11–13 year olds lied about their age to access restricted content (Kaspersky Lab, 2016).…”
Section: Digital Harmmentioning
confidence: 99%
“…Min et al (2021) seek to address whether the presence of a Free Trade Agreement between the United States and a foreign country significantly affect the outcomes of Internet domain name dispute arbitration cases, conducted within the framework of the Uniform Dispute Resolution Policy. The final article, Thurman and Obster (2021) focus on the type of content accessible to youth in the United Kingdom. Their survey of 16 and 17 year olds reveals that more than 63% had seen pornography on social media platforms than on pornographic websites, suggesting the UK government was right to target such platforms in its latest proposals.…”
Section: The Purpose Of Internet Regulation and Scholarshipmentioning
confidence: 99%